Age, psycho-emotional states and stress resistance in elite wrestlers - Korobeynikov, G.; Korobeinikova, L.; Shatskih, V. (International Journal of Wrestling Science, 2013)
In the last decade Olympic sports are characterized by the presence of older athletes who have reached high athletic results. The purpose of the study was to research the age peculiarities of stress resistance and psycho-emotional states in elite wrestlers. A total of 19 elite athletes (a span of ages), all members of the Ukrainian National Team in Greco-Roman wrestling were examined. The perception and processing of visual information, the balance of the nervous system and psycho-emotional stability were studied. The deterioration of neurodynamic functions in emotionally stressful situations was more evident in older age group compared with the younger age group due to age weakening of the afferent system of information perception, analysis, and processing. Conclusion: The connection between the age of elite athletes and stress resistance to psycho-emotional tension was recorded. In particular, it demonstrated considerable changes in heart rate regulation in the older age group when compared with the younger age group where the optimal reaction of heart rate regulation to psycho emotional tension was observed.